2020
DOI: 10.3390/cells9020427
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PARP-1, Histone H1 and SIRT-1 as New Regulators of Breast Cancer-Related Aromatase Promoter I.3/II

Abstract: Paracrine interactions between malignant estrogen receptor positive (ER+) breast cancer cells and breast adipose fibroblasts (BAFs) stimulate estrogen biosynthesis by aromatase in BAFs. In breast cancer, mainly the cAMP-responsive promoter I.3/II-region mediates excessive aromatase expression. A rare single nucleotide variant (SNV) in this promoter region, which caused 70% reduction in promoter activity, was utilized for the identification of novel regulators of aromatase expression. To this end, normal and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…A large systematic investigation of proteins that bind transcriptional enhancers and promoters in embryonic stem cells was carried out by exploiting chromatin immunoprecipitations (ChIP) by using antibodies for characteristic histone modifications and identification of associated proteins using mass spectrometry. The ChIP-MS method provided a detailed read-out of the transcriptional landscape representative of the investigated cell type, leading to the identification of several protein factors, most of which drive reprogramming to pluripotent stem cells such as Oct4 , Esrrb , Klf5 , Mycn , and Dppa2 .…”
Section: Chromatin Purification Methods Coupled With Mass Spectrometrymentioning
confidence: 99%
“…A large systematic investigation of proteins that bind transcriptional enhancers and promoters in embryonic stem cells was carried out by exploiting chromatin immunoprecipitations (ChIP) by using antibodies for characteristic histone modifications and identification of associated proteins using mass spectrometry. The ChIP-MS method provided a detailed read-out of the transcriptional landscape representative of the investigated cell type, leading to the identification of several protein factors, most of which drive reprogramming to pluripotent stem cells such as Oct4 , Esrrb , Klf5 , Mycn , and Dppa2 .…”
Section: Chromatin Purification Methods Coupled With Mass Spectrometrymentioning
confidence: 99%
“…PARP1 PARylates itself and histone H1, ejecting histone H1 from chromatin to activate gene expression and ultimately differentiation into neurons (Azad et al, 2018;Hau et al, 2017). Although this is gene-specific, it has been demonstrated that H1 and PARP1 compete on a genome-wide scale (Figure 3a), affecting gene expression patterns (Kaiser et al, 2020;Krishnakumar et al, 2008). In addition to histone H1, PARP1 also PARylates core histones, resulting in nucleosome destabilization, increased DNA accessibility (Martinez-Zamudio & Ha, 2012), and increased transcription (Kotova et al, 2022).…”
Section: Parp1's Regulation Of Chromatin Structure In Transcriptionmentioning
confidence: 99%
“…In primary mouse cortical neurons, KCl-induced depolarization results in H1 PARylation by PARP1, contributing to H1 release from chromatin and the simultaneous activation of immediate early gene (IEG) expression [ 50 ]. Activated PARP1 conducts PARylation and displacement of H1 from chromatin to form an euchromatin environment, leading to the activation of aromatase promoter I.3/II [ 51 ]. By using spFRET microscopy, PARP1 is found to interact with linker DNA of nucleosomes, promoting reorganization of the nucleosome, which is independent of PARylation activity [ 52 ].…”
Section: Parp1 and Chromatin Remodelingmentioning
confidence: 99%